2015
DOI: 10.1007/s11899-015-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Peripheral T Cell Lymphoma

Abstract: Understanding the molecular pathogenesis of peripheral T cell lymphomas (PTCLs) has lagged behind that of B cell lymphomas due to disease rarity. However, novel approaches are gradually clarifying these mechanisms, and gene profiling has identified specific signaling pathways governing PTCL cell survival and growth. For example, genetic alterations have been discovered, including signal transducer and activator of transcription (STAT)3 and STAT5b mutations in several PTCLs, disease-specific ras homolog family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…This is of therapeutic relevance since PTCL patients frequently exhibit transcriptional signatures associated to the activation of other STAT members like STAT1 and STAT5 (ref. 4 ), and STAT5B activating mutations have been described in PTCL subtypes 28 . In fact, despite the presence of the STAT3 Y640F mutation, OCI-Ly12 and OCI-Ly13.2 cells also showed baseline tyrosine phosphorylation of STAT1 and STAT5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of therapeutic relevance since PTCL patients frequently exhibit transcriptional signatures associated to the activation of other STAT members like STAT1 and STAT5 (ref. 4 ), and STAT5B activating mutations have been described in PTCL subtypes 28 . In fact, despite the presence of the STAT3 Y640F mutation, OCI-Ly12 and OCI-Ly13.2 cells also showed baseline tyrosine phosphorylation of STAT1 and STAT5 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we identified CDK7 as a critical transcriptional regulator required to maintain the malignant phenotype in PTCL. We demonstrated that CDK7 activity is necessary for STAT-dependent transcription, an approach that could benefit patients with tumours that present interleukin- or mutation-driven activation of STAT programs like in PTCL 22 23 28 41 or other malignances 42 43 . Importantly, we have identified the combination of THZ1 with BCL2 inhibitors as potential novel targeted agent-based therapeutic option for PTCL patients.…”
Section: Discussionmentioning
confidence: 96%
“…One recurrent translocation t(6;7)(p25.3;q32.3) is associated with the DUSP22 and IRF4 loci. The DUSP22 gene encodes a phosphatase, and its disruption is associated with upregulation of miR-29a and miR-29b on 7q32.3 [151]. ALK − ALCL has CD30 expression without ALK protein expression, likely a heterogeneous group of diseases classified by specific translocations [149,151].…”
Section: Pathophysiologymentioning
confidence: 99%
“…4 In AITL and PTCL, NOS, recurrent genetic alterations include those activating the T-cell receptor signaling pathway, such as RHOA mutations and CTLA4-CD28 fusions, and those affecting epigenetic-modifying genes, such as IDH2, TET2, and DNMT3A. [5][6][7][8][9] ALCLs have ALK fusion genes in about half of cases, leading to activation of the JAK-STAT3 signaling pathway. 4,10 Alternative mechanisms of JAK-STAT3 activation have been reported in anaplastic lymphoma kinase (ALK) 2 ALCLs, including mutations in JAK1 and/or STAT3 and fusions involving ROS1, TYK2, or FRK.…”
Section: Introductionmentioning
confidence: 99%